Almoner's report for six months, ending 30th June - Mudd, Edith E.
1902-11-19 1902 1900s 4 pages St. Georges Hospital W. 19th November 1902. ALMONER'S REPORT. For six months, ending 30th June. Number of Cases enquired into 1,375 Number judged and able to pay for treatment 133 Of these 133, there were 104 who did not return after being told more inquiry would be made. Twentyfour were found on enquiry able to pay, gave wrong addresses or permitted no enquiry. Only 4 were found, on enquiry unable to pay. Referred to clubs and Provident Dispensaries, about 270 Referred to Poor Law 12. Cases dealt with by the Charity Organisation Socty. 104 Of these 104, Twenty-two were assisted with convalesence and thirteen with surgical appliances and other forms of help. The rest were referred for Friendly visiting or enquiry. Help has been obtained from various other sources:- Invalid Childrens Aid 8 West London Society for Sick Children 3 Miss Holland's Convalescent Homes 9 Ragged School Union 3 Hospital Sunday Fund 4 Dr Barnardo 2 M.A.B.Y.S. 9 West London Mission 3 Helped by clergy etc. 7 48 Many patients are able to pay by instalments for their surgical appliances etc Of these I have not a very correct record. Convalescent treatment has been procured in 44 cases altogether of which 9 were sent to Open Air Sanatoria. Where open air treatment in particular be given, I do not think we give nearly enough importance to considering the 378/IMSW/A/1/4/7a